2005
DOI: 10.1152/ajpregu.00269.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin deficiency exaggerates intimal hyperplasia after vascular injury

Abstract: Decreased levels of tetrahydrobiopterin (BH4), an absolute cofactor for nitric oxide synthase (NOS), lead to uncoupling of NOS into a superoxide v. nitric oxide producing enzyme, and it is this uncoupling that links it to the development of vascular disease. However, the effects of in vivo deficiency of BH4 on neointimal formation after vascular injury have not been previously investigated. Hph-1 mice, which display 90% deficiency in guanine triphosphate cyclohydrolase I, the rate limiting enzyme in BH4 synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The authors suggest that aliskiren may restore eNOS uncoupling via augmenting tetrahydrobiopterin (BH 4 ) levels, an essential cofactor for eNOS. 7 This multidomain enzyme contains 2 functional regions: a flavin-containing reductase domain and a heme-containing oxygenase domain, which has binding sites for the triad of heme, L-arginine, and BH 4 . Between these 2 domains, there is a regulatory calmodulin-binding sequence.…”
mentioning
confidence: 99%
“…The authors suggest that aliskiren may restore eNOS uncoupling via augmenting tetrahydrobiopterin (BH 4 ) levels, an essential cofactor for eNOS. 7 This multidomain enzyme contains 2 functional regions: a flavin-containing reductase domain and a heme-containing oxygenase domain, which has binding sites for the triad of heme, L-arginine, and BH 4 . Between these 2 domains, there is a regulatory calmodulin-binding sequence.…”
mentioning
confidence: 99%
“…Previous investigations reported that BH4 stimulated proliferation of various cells, including vascular endothelial and pheochromocytoma (PC12) cells [18,24]. Moreover, BH4 deficiency is known to promote neointimal formation and cell proliferation in injured vascular walls [8]. It was reported that CCR2-stimulated kidney cell migration was inhibited in plasma or aorta homogenates in mice with elevated BH4 levels due to GTPCH overexpression [9], implying the possibility that BH4 may affect VMSC migration.…”
Section: Discussionmentioning
confidence: 99%
“…The salvage pathway can also generate BH4 from its oxidized forms via sepiapterin and SR [6]. The role of BH4 associated with NOS activity is generally relevant to the cardiovascular system in pathological and physiological conditions, including hypertension, cardiac hypertrophy, and vascular remodeling [7][8][9]. Recently, we found that deficiency in BH4 regeneration caused by diminished DHPR expression is involved in vascular disorders in hypertensive rats [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliskiren may restore eNOS uncoupling via augmenting tetrahydrobiopterin (BH 4 ) levels, an essential cofactor for eNOS. 29 This multidomain enzyme contains 2 functional regions: a fl avin-containing reductase domains and a heme-containing oxygenase domain, which has binding sites for the triad of heme, L-arginine, and BH 4 . Between these 2 domains, there is a regulatory calmodulin-binding sequence.…”
Section: Effect Of Aliskiren On Endothelial Functionmentioning
confidence: 99%